The Role of Digital Marketing in Technology-Based MSME Development Efforts - Ragil Almaliki; Ifah Rofiqoh (Jurnal Ekuisci, 2025)
Purpose. This study aims to analyze the role of digital marketing in the development of technology-based Micro, Small, and Medium Enterprises (MSMEs) in Indonesia. Method. Using a literature review approach of 15 scientific articles published from 2015 to 2024, this study identifies effective digital marketing strategies, challenges in their implementation, and opportunities that can be taken advantage of by MSME actors. Result. The results of the study show that strategies such as the use of social media (Instagram, TikTok), Search Engine Optimization (SEO), storytelling, and partnerships with local influencers contribute significantly in increasing business visibility, customer engagement, and sales turnover. Conclusion. Limited digital literacy, inadequate human resources, and changes in digital platform algorithms are still major challenges. Implementation. This study recommends the need for structured digital assistance, cross-sector collaboration, and ecosystem development that supports the digital transformation of MSMEs in a sustainable manner.